2017
DOI: 10.1039/c7ew00074j
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of 2D functional covalent–organic framework membranes for water desalination

Abstract: A computational study is reported for water desalination through 2D covalent–organic framework membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 38 publications
2
83
0
Order By: Relevance
“…Meanwhile, 400 nm–5 μm films were prepared by drop‐casting suspensions of equivalent concentrations (Figure A, Figure S12). Such fine control of film thickness has not been achieved by interfacial polymerization or solvothermal synthetic methods, thus making this approach ideal for fabricating membranes for chemical‐separation applications, where the film thickness and pore size define the performance of the material …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, 400 nm–5 μm films were prepared by drop‐casting suspensions of equivalent concentrations (Figure A, Figure S12). Such fine control of film thickness has not been achieved by interfacial polymerization or solvothermal synthetic methods, thus making this approach ideal for fabricating membranes for chemical‐separation applications, where the film thickness and pore size define the performance of the material …”
Section: Resultsmentioning
confidence: 99%
“…[254] Zhang et al computationally designed a series of 2D functional TpPa-1 COF and found that hydrophilic functional groups are essential in improving water permeance with an over 98% salt rejection. [255] To promote the sieving effects and mechanical strength of COF membranes, 1D cellulose nanofibers (CNFs) were integrated into the membrane (Figure 12c). [247] The pore size (0.45-1.0 nm) that rendered membrane precise molecular sieving ability was obtained.…”
Section: Desalinationmentioning
confidence: 99%
“…Such fine control of film thickness has not been achieved by interfacial polymerization or solvothermal synthetic methods, [11,18,24] thus making this approach ideal for fabricating membranes for chemical-separation applications,w here the film thickness and pore size define the performance of the material. [44][45][46] Crystalline films were fabricated from two additional imine-linked COF powders (TAPB-PDACOF,Methyl COF, Schemes S2, S3), thereby establishing the generality of the method. In each case,the pristine COF powder was exfoliated through stirring and sonication in the presence of TFA.…”
Section: Resultsmentioning
confidence: 99%